Kesiapan guru matematika sekolah menengah pertama dalam melaksanakan Kurikulum 2013 - Khikayah, Khikayah (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2018)
Penelitian ini bertujuan untuk mengungkap kesiapan guru matematika SMP negeri di Kabupaten Cilacap dalam melaksanakan Kurikulum 2013, terdiri dari: pengetahuan guru tentang pembelajaran matematika Kurikulum 2013, upaya yang dilakukan guru untuk meningkatkan pemahaman terhadap pembelajaran matematika Kurikulum 2013, sikap guru terhadap pelaksanaan Kurikulum 2013, perencanaan pelaksanaan pembelajaran matematika yang sesuai dengan Kurikulum 2013, dan ketersediaan sarana dan prasarana sekolah yang menunjang pelaksanaan Kurikulum 2013. Penelitian ini merupakan penelitian survei yang menggunakan pendekatan kuantitatif dengan didukung pendekatan kualitatif. Sampel penelitian ini adalah 31 guru ditentukan dengan teknik stratified purposive sampling. Pengumpulan data dilaksanakan melalui angket, wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukan bahwa kesiapan guru matematika SMP negeri di Kabupaten Cilacap termasuk kriteria cukup. Kesimpulan tersebut didukung oleh komponen: pengetahuan guru tentang pembelajaran matematika Kurikulum 2013 yang termasuk kriteria cukup; upaya yang dilakukan guru untuk meningkatkan pemahaman terhadap pembelajaran matematika Kurikulum 2013 yang termasuk kriteria kurang; sikap guru terhadap pelaksanaan Kurikulum 2013 yang termasuk kriteria cukup; perencanaan pelaksanaan pembelajaran matematika yang sesuai dengan Kurikulum 2013 yang termasuk kriteria cukup; dan ketersediaan sarana dan prasarana sekolah yang menunjang pelaksanaan Kurikulum 2013 yang termasuk kriteria kurang. The readiness of mathematics teachers of state junior high schools to implement curriculum 2103 AbstractThis study aims to reveal the readiness of mathematics teachers of state junior high schools (SJHS's) in Cilacap Regency in implementing Curriculum 2013, consisting of:  teachers' knowledge of the teaching of mathematics in Curriculum 2013, the teachers' efforts to improve their understanding of the teaching of mathematics in Curriculum 2013,  the teachers'attitudes towards the implementation of Curriculum 2013,  the planning of the implementation of teaching mathematics in accordance with Curriculum 2013, and the availability of facilities that support the implementation of Curriculum 2013. This study was a survey that used the quantitative approach supported by the qualitative approach. A sample of this study was 31 teachers using the stratified purposive sampling technique. The data were collected through questionnaires, interviews, observation, and documentation. The data were analyzed using the quantitative and qualitative descriptive techniques. The results of the research show that the readiness of mathematics teachers of state junior high schools in Cilacap Regency is included in the sufficient criterion. These conclusions are supported by the following components: the teachers'knowledge of the teaching of mathematics in Curriculum 2013, which is in the sufficient criterion; the teachers'efforts to improve their understanding of teaching mathematics in Curriculum 2013, which is in the insufficient criterion; the teachers'attitudes towards the implementation of Curriculum 2013, which is in the sufficient criterion; the planning the implementation of teaching mathematics in accordance with Curriculum 2013 which is in the sufficient criterion, and the availability of facilities that support the implementation of Curriculum 2013, which is in of the insufficient criterion.